TWO-LEVEL OPTIMAL CONTROL DESIGN - Lysenko, A.I.; Kazak, V.N.; Chekanova, I.V. (Proceedings of National Aviation University (archive), 2005)
The method of analytical design of the two-level optimal control algorithm is considered here together with using of the functional of the work generalized. The method offered may be used not only at the stage of preliminary synthesis of branching trajectories but for operative trajectories optimization of compound dynamic systems as well. The method of two-level tasks solution considered here may be extended to other objects of control.